147 What are the main concerns of participants in a drug trial for chronic breathlessness?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Singh, S; Lovell, N; Yi, D; Higginson, IJ
Abstract : Background: Chronic breathlessness is a common, distressing advanced illness symptom. Previous work has synthesised patient concerns, but not specifically within a trial setting. Aims: To determine the main concerns of participants in a drug trial for chronic breathlessness and assess change during the trial. Methods: Data was collected as part of a multi-centre randomised placebo controlled, double-blind feasibility trial of Mirtazapine for patients with chronic breathlessness (ISRCTN 33236160 ). The question 'What have been your main concerns or problems over the past 3 days?' as part of the Integrated Palliative Outcomes Scale (IPOS) was asked at three time-points (baseline, day 14, day 28). Participants were able to provide up to three answers. A free text analysis was done, and concerns were categorised using the domains of total breathlessness. Results were compared across the time-points of the trial to assess for change. Results: 64 patients participated in the trial. 73% were male; median age 72 years (range 51–90). 63% had a diagnosis of chronic obstructive pulmonary disease, 30% interstitial lung disease, and 8% chronic heart failure or cancer. 267 responses were collected. The most commonly reported concerns were breathlessness (n=46 baseline, n=20 day 14, n=28 day 28), fatigue (n=7 baseline, n=6 day 14, n=6 day 28) and mobility (n=4 baseline, n=7 day 14, n=4 day 28). Using the model of total breathlessness, 81% of concerns were categorised within the physical domain. 23% as psychological, 6% spiritual, and 3% social. 35/267 concerns showed overlap across multiple domain. Conclusion: Physical concerns, specifically breathlessness, fatigue and mobility were most common. Concerns appeared to remain stable during the trial period. It is crucial that outcome measures which reflect the concerns of patients are selected.